The normative role of the corporately owned community newspapers in the digital era: District Mail, Northern News and Eikestad Nuus in South Africa - Dinabantu, Keith Sindile (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.